2018
DOI: 10.1016/j.sjbs.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of leucine-rich repeat-containing G protein-coupled receptor 5 predicts poor prognosis in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignancies and the fifth leading cause of cancer-related death worldwide. Novel prognostic biomarkers are urgently needed for patients with HCC. Leucine-rich repeat-containing G-protein coupled receptor 5 (LGR5) overexpression may promote tumor metastasis in HCC. However, few studies investigate the prognosis predictive role of LGR5 in patients with HCC. Herein, we aimed to examine the expression level of LGR5 in tumors and its correlation with clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…(20,(42)(43)(44) In addition, recent studies have demonstrated that LGR5 increases OLFM4 expression through the Wnt signaling pathway and promotes stem cell property in the intestine. (27)(28)(29) LGR5 is reported to be expressed in HCC (45,46) ; however, no reports have focused on the interaction between LGR5 and OLFM4. Moreover, no previous studies have shown the effects of LGR5 or OLFM4 on cancer stem cell-like property in any malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…(20,(42)(43)(44) In addition, recent studies have demonstrated that LGR5 increases OLFM4 expression through the Wnt signaling pathway and promotes stem cell property in the intestine. (27)(28)(29) LGR5 is reported to be expressed in HCC (45,46) ; however, no reports have focused on the interaction between LGR5 and OLFM4. Moreover, no previous studies have shown the effects of LGR5 or OLFM4 on cancer stem cell-like property in any malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the most common malignancies and ranks as the second leading cause of cancer-associated mortality worldwide [ 1 3 ]. Furthermore, HCC patients have a poor prognosis, with a 5-year survival rate of 18% [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…EMT is associated with diverse tumor including breast cancer and pancreatic cancer 43,44. EMT in HCC caused by high expression of Lgr5 partly blame for a poor prognosis in HCC patient 27. So we play attention to the effect of Lgr5 on drug resistance.…”
Section: Discussionmentioning
confidence: 99%